2011
DOI: 10.1111/j.1467-8535.2010.01113.x
|View full text |Cite
|
Sign up to set email alerts
|

SimPharm: How pharmacy students made meaning of a clinical case differently in paper‐ and simulation‐based workshops

Abstract: Several scholars contend that learning with computer games and simulations results in students thinking more like professionals. Bearing this goal in mind, we investigated how a group of pharmacy students learnt with an in-house developed computer simulation, SimPharm. Adopting situated cognition as our theoretical lens, we conducted a case study involving 20 undergraduate students to tease out how they made meaning of a clinical case differently in two different contexts: a typical paper-based workshop and on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 23 publications
(15 reference statements)
1
19
0
Order By: Relevance
“…International literature continues to reinforce the need for and the positive effects associated with the use of simulation-based methodologies as part of pharmacy educational programs (Kirwin et al 2013;Loke et al 2011;Murdoch et al 2014;Regan et al 2014;Ruehter et al 2012;Salter et al 2014;Smith and Benedict 2015;Veettil and Rajiah 2016;Vyas et al 2013). However, there is limited information on Australian studies that involved the development, implementation, and evaluation of hospital-based simulation training packages within tertiary education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…International literature continues to reinforce the need for and the positive effects associated with the use of simulation-based methodologies as part of pharmacy educational programs (Kirwin et al 2013;Loke et al 2011;Murdoch et al 2014;Regan et al 2014;Ruehter et al 2012;Salter et al 2014;Smith and Benedict 2015;Veettil and Rajiah 2016;Vyas et al 2013). However, there is limited information on Australian studies that involved the development, implementation, and evaluation of hospital-based simulation training packages within tertiary education.…”
Section: Discussionmentioning
confidence: 99%
“…International literature emphasizes the need to utilize an assortment of technology-based learning environments to train and educate health professionals (Cook et al 2011;Keppell et al 2015) and specifically for pharmacists (Fejzic and Barker 2015;Smith and Benedict 2015). Multiple studies support embedding technology-enhanced, simulation-based education into pharmacy curricula, such as online learning that is enriched by pre-recorded role plays with actors or simulated participants, virtual patients, task simulations and/or interactive platforms that simulate a specific skill or competency (Fejzic and Barker 2015;Kirwin et al 2013;Loke et al 2011;Regan et al 2014;Salter et al 2014;Smith and Benedict 2015;Veettil and Rajiah 2016;Vyas et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…37 Cook et al concluded the role of virtual patients in postgraduate and continuing education requires further study. 22 Much of the literature looks at teaching students clinical skills with chronic disease conditions 25,[38][39][40][41][42][43] or determines student satisfaction with the learning experience 44,45 and the perceived value and useability of the virtual patient tools. 46 Our research looked at not only increasing knowledge but improving confidence with a challenging patient American Journal of Pharmaceutical Education 2016; 80 (3) Article 48.…”
Section: Discussionmentioning
confidence: 99%
“…The health care literature emphasizes the importance of health care students, including pharmacy students, undergoing specific training using a technological approach, such as using virtual patient software programs, to ensure the provision of high quality care to patients with chronic disease. 21,23,[27][28][29][30][31] Therefore, the introduction of virtual patients to pharmacy education can potentially offer an effective method for teaching students, posing a challenge to current pharmacy educators to master and adopt these methods.…”
Section: Discussionmentioning
confidence: 99%